Mechanisms Underlying Hox-Mediated Transcriptional Outcomes - Cain, Brittany; Gebelein, Brian (Frontiers in Cell and Developmental Biology, 2021)
Metazoans differentially express multiple Hox transcription factors to specify diverse cell fates along the developing anterior-posterior axis. Two challenges arise when trying to understand how the Hox transcription factors regulate the required target genes for morphogenesis: First, how does each Hox factor differ from one another to accurately activate and repress target genes required for the formation of distinct segment and regional identities? Second, how can a Hox factor that is broadly expressed in many tissues within a segment impact the development of specific organs by regulating target genes in a cell type-specific manner? In this review, we highlight how recent genomic, interactome, and cis-regulatory studies are providing new insights into answering these two questions. Collectively, these studies suggest that Hox factors may differentially modify the chromatin of gene targets as well as utilize numerous interactions with additional co-activators, co-repressors, and sequence-specific transcription factors to achieve accurate segment and cell type-specific transcriptional outcomes.